Implementasi Corporate Social Responsibility (CSR) pada PT. Maritim Barito Perkasa Banjarmasin - Refli Sinus Tumbio; Irwansyah Irwansyah; Taharuddin Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
The purposes of this study were to determine the implementation of Corporate Social Responsibility (CSR) conducted by PT. Maritim Barito Perkasa Banjarmasin and some constraints encountered by the company.This was a qualitative research method. A qualitative research is used to describe, express and understand the issues arisen from the implementation of Corporate Social Responsibility (CSR) at PT. Maritim Barito Perkasa Banjarmasin.The results of this study were the implementation of Corporate Responsibility (CSR) conducted by PT. Maritim Barito Perkasa Banjarmasin in which the company conduct some strategic management to determine CSR programs, procedures and budgets. The Programs are: 1). Scholarship program; 2).Micro, Small and Medium-sized Enterprises (also known as SMEs) programs; 3).Early childhood/ kindergarten teacher straining program; 4). Apprentice ship Student Program; 5).General Program, which consist of: a). MPB “Baelang”; b).Fasting break during Ramadhan for 100 Orphans; c). Provide livestock for “Qurban”; d).Giving support for Christmas; e). Renovation of Worship Place; f).School Renovation; g). Mass circumcision; h). Maternal and child health services in IHC; i). Blood donors; j). Giving some donation for surrounding area of the company primarily to educational institutions. The procedure is by receiving proposals from “Pamswakarsa” around the company area, surveying, conducting FGD (Focus Group Discussion) and socialization.eywords: Implementation, Corporate Social Responsibility